Expression of CLAVATA3 fusions indicates rapid intracellular processing and a role of ERAD. (June 2018) - De Marchis, Francesca; Colanero, Sara; Klein, Eva M.; Mainieri, Davide; Prota, Viviana M.; Bellucci, Michele; Pagliuca, Giampiero; Zironi, Elisa; Gazzotti, Teresa; Vitale, Alessandro; Pompa, Andrea
Highlights: Tobacco expressing CLAVATA3-GFP (CLV3-GFP) secretes the active CLV3 peptide. The ER chaperone endoplasmin supports CLV3-GFP synthesis. Intact CLV3-GFP is rapidly degraded, also when intracellular traffic is inhibited. CLV3-GFP half-life is extended by inhibitors of ER associated degradation (ERAD). We propose that ERAD regulates the synthesis of the active CLV3 peptide. Abstract: The 12 amino acid peptide derived from the Arabidopsis soluble secretory protein CLAVATA3 (CLV3) acts at the cell surface in a signalling system that regulates the size of apical meristems. The subcellular pathway involved in releasing the peptide from its precursor is unknown. We show that a CLV3-GFP fusion expressed in transfected tobacco protoplasts or transgenic tobacco plants has very short intracellular half-life that cannot be extended by the secretory traffic inhibitors brefeldin A and wortmannin. The fusion is biologically active, since the incubation medium of protoplasts from CLV3-GFP-expressing tobacco contains the CLV3 peptide and inhibits root growth. The rapid disappearance of intact CLV3-GFP requires the signal peptide and is inhibited by the proteasome inhibitor MG132 or coexpression with a mutated CDC48 that inhibits endoplasmic reticulum-associated protein degradation (ERAD). The synthesis of CLV3-GFP is specifically supported by the endoplasmic reticulum chaperone endoplasmin in an in vivo assay. Our results indicate that processing of CLV3 starts intracellularly in an early compartment of the secretory pathway and that ERAD could play a regulatory or direct role in the active peptide synthesis.